EVALUATION OF THE EFFECTIVENESS OF THE GRATIFICATION CONTROL PROGRAM IN PREVENTING CONFLICT OF INTEREST: A STRATEGIC STUDY IN THE CENTRAL PAPUA PROVINCE INSPECTORATE - Douw, Ida Rohayati; Lambe, Kristian Hoegh Pride; Pasae, Yoel (Journal of Entrepreneur, Business and Management, 2024)
This study evaluates the effectiveness of the Gratification Control Program in preventing conflicts of interest in the Inspectorate of Central Papua Province. Using a qualitative approach, data were collected through observation, interviews, and documentation with seven employees as informants. The results of the study indicate that this program reflects a strong commitment to preventing corruption through socialization, training, and clear operational guidelines. However, its effectiveness still needs to be improved due to lack of employee understanding, low participation, and minimal management support. With regular evaluation and compliance with policies, this program has the potential to create a cleaner and more accountable government.